Transcultural Lifestyle Medicine in Type 2 Diabetes Care: Narrative Review of the Literature - González-Rivas, Juan P; Pavlovska, Iuliia; Polcrova, Anna; Nieto-Martínez, Ramfis; Mechanick, Jeffrey I (American journal of lifestyle medicine, 2023)
Disparities in type 2 diabetes (T2D) care is a global problem across diverse cultures. The Dysglycemia-Based Chronic Disease (DBCD) model promotes early and sustainable interventions along the insulin resistance (stage 1), prediabetes (stage 2), T2D (stage 3), and complications (stage 4) spectrum. In this model, lifestyle medicine is the cornerstone of preventive care to reduce DBCD progression and the socioeconomic/biological burden of disease. A comprehensive literature review, spanning 2000 to 2021, was performed and 55 studies were included examining the effects of lifestyle medicine and their cultural adaptions with different prevention modalities. In stage 1, primordial prevention targets modifiable primary drivers (behavior and environment), unhealthy lifestyles, abnormal adiposity, and insulin resistance with educational and motivational health promotion activities at individual, group, community, and population-based scales. Primary, secondary, and tertiary prevention targets individuals with mild hyperglycemia, severe hyperglycemia, and complications, respectively, using programs that incorporate structured lifestyle interventions. Culturally adapted lifestyle change in primary and secondary prevention improved quality of life and biomarkers, but with a limited impact of tertiary prevention on cardiovascular events. In conclusion, lifestyle medicine with cultural adaptations is an integral part of preventive care in patients with T2D. However, considerable research gaps exist, especially for tertiary prevention.
Keywords: dysglycemia; type 2 diabetes; transcultural; culture; lifestyle medicine; prevention